An Overview of the Role of Molecular Chaperones in Protein Homeostasis - O. Tiroli-Cepeda, Ana; H.I. Ramos, Carlos (Protein and Peptide Letters, 2011)
Cells require a protein quality control (PQC) system to obtain a correct balance between folding and the degradation of incorrectly folded or misfolded proteins. This system maintains protein homeostasis and is essential for life. Key components of the PQC are molecular chaperones, which compose a ubiquitous class of proteins that mediate protein quality control by aiding in both the correct folding of proteins and the elimination of proteins that are misfolded due to cellular stress or mutation. Recent studies showed that protein homeostasis has an important role in nutrition and aging, increasing the relevance of the heat shock response to human health. This review summarizes our current knowledge of the molecular chaperone system and its role in protein homeostasis.
Keywords: ER